Методы оценки и прогнозирование последствий при разрушении гидротехнических сооружений - Striganova, Марина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
In emergency situations on the water bodies waterfront feature of the destruction of hydraulic structures is the formation of waves breaking. As a result, simulation of unsteady flow in the destruction of the dam and the formation of waves breaking and experimental studies in laboratory prismatic tray developed a method of forecasting the dynamics parameters of the wave break, which allows to plot the passage of waves breaking on the watercourse and to determine the flood zone, thus enhancing the effectiveness of measures to protect people and objects in the hydrodynamic accidents.